2017
DOI: 10.1590/1807-3107bor-2017.vol31.0070
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal impact of clinical and socioenvironmental variables on oral health-related quality of life in adolescents

Abstract: The aim of the present study was to investigate the impact of oral diseases, socioeconomic status, and family environmental factors on changes in the perception of oral health-related quality of life (OHRQoL) in adolescents. A prospective cohort study was conducted in Juiz de Fora, Minas Gerais, Brazil, with a sample of 286 twelve-year-old adolescents from public and private schools, selected by means of multistage random sampling. The adolescents were clinically examined for dental caries experience (number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
2
28
0
4
Order By: Relevance
“…However, there were no statistical differences between the participants and dropouts, and previous studies have reported higher nonresponse rates among adolescents. 40,41 In addition, dropouts were equally distributed among all enrolled schools, thus providing representativeness and a form of comprehension on oral health inequalities in adolescence. Our study only included adolescents who were enrolled in public schools.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no statistical differences between the participants and dropouts, and previous studies have reported higher nonresponse rates among adolescents. 40,41 In addition, dropouts were equally distributed among all enrolled schools, thus providing representativeness and a form of comprehension on oral health inequalities in adolescence. Our study only included adolescents who were enrolled in public schools.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were enrolled consecutively (May of 2016 to December of 2016), and they were interviewed 30 days following the end of the dental treatment 29 and after they had answered the final Children Perception Questionnaire (CPQ [11][12][13][14]. All interviews were carried out in a comfortable non-clinical office setting next to the waiting area of the dental clinic.…”
Section: Qualitative Interview Studymentioning
confidence: 99%
“…10 Several studies, however, have demonstrated that Brazilian adolescents have a high dental treatment needs 11 and tend to report relative poor oral health and a low OHRQoL in terms of oral symptoms, functional limitations, and emotional and social well-being. [12][13][14][15] Hence, there is scarce information on how dental treatment could help to improve the adolescents' OHRQoL, [16][17][18][19] and on how adolescents experience quality of life. [20][21][22] The use of a qualitative approach into the evaluation of health perceptions may unravel the extent to which social and emotional aspects are being adequately described and understood by the quantitative instruments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations